2011
DOI: 10.1002/jrs.2991
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐nanoparticle‐coating‐induced enhancement and weakening of resonant Raman scattering in ZnO: effect of surface electric field

Abstract: Effects of Ag and Ti nanoparticle coatings on resonant Raman scattering in various ZnO thin films are presented. The longitudinal optical (LO) phonons, irrespective of the ZnO quality, exhibit an enhancement and a weakening by the Ag and Ti nanoparticle coatings, respectively. The enhancement (weakening) is always accompanied by a reduced (an increased) intensity ratio of the second to first-order LO phonons, which can be associated with changes in the electron-phonon coupling strength in the probed area of Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It is well reported that this peak has strong dependence on the surface electric field and hence can be modulated using metal NPs. 79 Interestingly both broadening and increase in the intensity of the peak corresponding to E 1 (LO) mode was observed in case of Cr coated ZnO NRs (Cr coating for 10 seconds), clearly demonstrating the fact that electron–phonon coupling strength is diminishing in case of coating of Cr. The peaks at 525 and 564 cm −1 can be assigned to 2LA and A 1 (LO) modes respectively.…”
Section: Resultsmentioning
confidence: 85%
“…It is well reported that this peak has strong dependence on the surface electric field and hence can be modulated using metal NPs. 79 Interestingly both broadening and increase in the intensity of the peak corresponding to E 1 (LO) mode was observed in case of Cr coated ZnO NRs (Cr coating for 10 seconds), clearly demonstrating the fact that electron–phonon coupling strength is diminishing in case of coating of Cr. The peaks at 525 and 564 cm −1 can be assigned to 2LA and A 1 (LO) modes respectively.…”
Section: Resultsmentioning
confidence: 85%
“…Because the more amount of metal nanoparticles in metal/ZnO heterostructures induce the more electrons transfer between Au/Ti and ZnO nanobelts. The improved Raman scattering activity is mainly attributed to the strong local electromagnetic field enhancement on the surface of ZnO nanobelts due to the LSP coupling resonance effect of adjacent metal nanoparticles, and dependent on the metal nanoparticle size [40][41][42][43][44][45][46].…”
Section: Resultsmentioning
confidence: 99%
“…Nano-sized particles and presence of imperfections and/or impurities result in breakdown of phonon momentum selection rules, thus making some forbidden vibration modes to contribute to Raman scattering. The relative intensity of this contribution is higher in the case of ZnO/Ag [26].…”
Section: Xps and Raman Analysesmentioning
confidence: 88%